Photoinduced C-C Cross-Coupling of Aryl Chlorides and Inert Arenes - Lele Wang; Wenzhao Qiu; Hongge Shao; Rusheng Yuan (International Journal of Photoenergy)
Here we report a facile, efficient, and catalyst-free method to realize C-C cross-coupling of aryl chlorides and inert arenes under UV light irradiation. The aryl radical upon homolytic cleavage of C-Cl bond initiated the nucleophilic substitution reaction with inert arenes to give biaryl products. This mild reaction mode can also be applied to other synthetic reactions, such as the construction of C-N bonds and trifluoromethylated compounds.